Evaluasi Pembelajaran Melalui Aplikasi Quizizz Pada Materi IPS Kelas IX SMP Negeri 1 Cigombong - Susilo, Edy; Hamida, Khairina; Hamida, Jaminah; Sudrajat, Yayan (SINAU: Jurnal Ilmiah Pendidikan Dan Pembelajaran, 2022)
Various problems faced by teachers, students and parents while studying during the pandemic. Teachers find it difficult to give assessments so students do schoolwork at home. Therefore there is a need for innovation in giving assignments to be more fun and not burdensome. One such innovation is using quizizz. This service aims to evaluate student learning materials. This activity was attended by 29 students at SMP Negeri 1 Cigombong. From the results of online quizzes using the quizizz application, the teacher knows how much students understand in learning and also as a social studies subject value tool for teachers.